Metagenomic Next-Generation Sequencing of Cerebrospinal Fluid for the Diagnosis of Cerebral Aspergillosis - Xing, Xiao-Wei; Yu, Su-Fei; Zhang, Jia-Tang; Tan, Rui-Shu; Ma, Yu-Bao; Tian, Xia; Wang, Rong-Fei; Yao, Guo-En; Cui, Fang; Gui, Qiu-Ping; Yu, Sheng-Yuan (Frontiers in Microbiology, 2021)
Purpose: Cerebral aspergillosis (CA) is a rare but often fatal, difficult-to-diagnose, opportunistic infection. The utility of metagenomic next-generation sequencing (mNGS) for diagnosis of CA is unclear. We evaluated the usefulness of mNGS of the cerebrospinal fluid (CSF) for the diagnosis of CA. Methods: This prospective study involved seven consecutive patients with confirmed CA in whom CSF mNGS was performed. Serum (1→3)-β-D-glucan and galactomannan levels were determined, and histopathological examination and mNGS of the CSF were conducted. CSF specimens from three non-infected patients were used as positive controls. Results: mNGS of the CSF was positive in six of the seven confirmed CA cases (85.71% sensitivity). In the cryptococcal meningitis group (control), mNGS of the CSF was positive for Aspergillus in two patients (84.62% specificity). The positive likelihood ratio, negative likelihood ratio, and Youden’s index of mNGS for CA in the CSF were 5.565, 0.169, and 0.7, respectively. Among the six mNGS-positive cases, more than two Aspergillus species were found in four (4/6, 66.67%). In the positive controls, the addition of one A. fumigatus spore yielded a standardised species-specific read number (SDSSRN) of 25.45 by mNGS; the detection rate would be 0.98 if SDSSRN was 2. Conclusion: mNGS facilitates the diagnosis of CA and may reduce the need for cerebral biopsy in patients with suspected CA. Trial Registration Number: Chinese Clinical Trial Registry, ChiCTR1800020442.